The pathogenesis of disseminated intravascular coagulation and the role of microparticles and tissue factor in acute promyelocytic leukemia (Research, Society and Development, 2023)
Objective: To perform an integrative review of the literature in order to raise data that clarify the pathogenesis of Disseminated Intravascular Coagulation (DIC) and the role of microparticles and tissue factor in Acute Promyelocytic Leukemia (APL). Method: This study is an integrative literature review that is based on the search of articles in databases, Pub Med, Science Direct, Scielo, journals and websites, with the following descriptors in "Acute Promyelocytic Leukemia", "Disseminated Intravascular Coagulation", "Hypogranular Promyelocytic Leukemia", "Hypergranular Promyelocytic Leukemia", "Microparticles", "Tissue Factor", using articles of original research between the years 2002 to 2022. This literature survey was conducted in the period from 02/01/2022 to 12/23/2022. Results: From a total of 137 articles identified, the following were excluded: 57 for not fitting the inclusion criteria, 32 by title analysis, and 14 by abstract analysis. Thirty-four articles remained that were analyzed in their entirety, of which 29 were excluded, thus, only 5 were included in the study. Discussion: The analysis of the studies selected in the review shows that the relationship between the pathophysiology of coagulopathy associated with ALI is complex, and the main mechanism is mediated by specific properties of the leukemic cell itself, which releases several mediators capable of activating the VSD. Conclusion: It is concluded that the CIVD that occurs in ALI patients is due to the activation of hemostasis by microparticles that carry tissue factor and are present in the promyelocytes. This understanding is critical to establishing effective treatment protocols.